Live Demonstration: Real-Time Vi-SLAM With High-Resolution Event Camera - Yang, Gongyu; Ye, Qilin; He, Wanjun; Zhou, Lifeng; Chen, Xinyu; Yu, Lei; Yang, Wen; Chen, Shoushun; Li, Wei (IEEE Computer Society Conference on Computer Vision and Pattern Recognition workshops, 2019)
Event camera is bio-inspired vision sensors that output pixel-level brightness changes asynchronously. Compared to the conventional frame-based camera, it is with high dynamic range, low latency and high sensitivity, and thus can be exploited in SLAM to tackle the problem of occasions with high-speed camera moving and low-light scenes. In this demo, we implement the visual-inerial SLAM in real time with the recently released event camera, namely, CeleX-V. With the feature of high spatial resolution (1280x800) and low latency <0.5us, the proposed method can provide frames with abundant textures and high time response, which leads to more stable tracking ability and better performance in SLAM system.